Effect of low-intensity pulsed ultrasound combined with Rhodiola rosea on proliferation and differentiation of osteoblasts: Ultrasound and Rhodiola rosea on osteoblasts' growth and differentiation - Zhang, Lanjun; Yuan, Hang; Tong, Yongjun; Zhang, Yu; Sun, Yu; Li, Yan (Cellular and Molecular Biology, 2023)
Osteoblasts (OB), as the mesenchymal progenitor cells differentiated from the inner and outer periosteum and the stroma in bone marrow, can specifically secrete a variety of bioactive substances, thereby regulating and influencing the process of bone formation and reconstruction. Therefore, promoting the proliferation and differentiation of OB plays an important role in promoting bone formation. Based on this, this study studied the proliferation and differentiation of OB by low-intensity pulsed ultrasound (LIPUS) combined with Rhodiola rosea to provide a reliable theoretical basis for bone repair. In this study, rat OB was used as the research material and divided into groups A, B, C and D according to different intervention methods after osteogenic culture. Joint Salvia miltiorrhiza LIPUS ever seen from the results of the study promotes the strongest OB proliferation, at the same time, effectively reduces the apoptosis rate of the OB and apoptosis-related proteins expression, and promotes the OCN and ALO protein expression, indicated by LIPUS Salvia miltiorrhiza can effectively promote the osteoblast proliferation, differentiation, in order to promote cartilage repair and bone strengthen provides an effective means.